Management and characterization of water resources in the community of Barro Preto in the municipality of Santa Maria de Itabira MG (Research, Society and Development, 2019)
The low availability of some studies on the water resources situation of the quilombola population of Barro Preto in the municipality of Santa Maria de Itabira MG, the parameters of water quality in the village were analyzed in the field, soil use and occupation and some anthropogenic actions of the consumption to the discharge of sewage in the Barro Preto stream. In this way, this article aimed to analyze the management of community water resources for water supply and water quality upstream and downstream of the Barro Preto. For this reason, the research was carried out in a qualitative and quantitative way, in a descriptive way by field surveys on the use and soil occupation in the community of Barro Preto. Thus, observation and experimental research were used as data collection, using as a unit of analysis the spring water course. Through field research, the disordered forms of land use and occupation were identified, such as the raising of cattle in places that should be from riparian forests, the proximity of houses to the stream with direct disposal of raw sewage. The water analysis showed a precarious state of the spring with interferences in the O² rates and the presence of pathogenic organisms like Escherichia coli, that can cause diseases to the population of the water consumer of the Barro Preto stream.